Pembuatan Alat Pengolahan Limbah Tekstil di Kecamatan IV Nagari Bayang Utara Painan, Pesisir Selatan - Pelita, Elda; Suciati, Dwimaryam; Anwar, Hazil; Nirmala, Dyah; Youfa, Rita; Desniorita, Desniorita; Jayanti, Regna Tri; Sahaq, Anang Baharuddin; Permadani, Resi Levi (Politeknik ATI Padang, 2024)
Batik Jembatan Akar Small and Medium Industry (IKM) endeavors to produce Root Bridge batik fabric, which is a defining feature of the IV Nagari Bayang Utara sub-district. In its production process, IKM Batik Jembatan Akar still relies on rudimentary and traditional equipment and lacks the means to handle textile waste, leading to its disposal in nearby ditches. While the current waste output may not be significant, its continuation poses a threat to the local environment. Insufficient awareness of the environmental impact of textile waste can result in environmental pollution issues and disrupt community harmony around IKM Jembatan Akar. Additionally, IKM Batik Jembatan Akar struggles to stimulate consumer interest in traditional batik amidst the abundance of low-priced printed alternatives. The limited demand for production means that this SME has yet to invest in technology and waste processing equipment for its batik cloth production. Politeknik ATI Padang Community Service initiative seeks to educate all IKM Batik Jembatan Akar employees on the importance of waste processing and online marketing strategies, while providing training on donated textile waste processing equipment to enhance sales value and mitigate environmental harm. The approaches employed in this community service endeavor include (1) comprehensive activity planning, encompassing location surveys, production assessments, and inventory checks; (2) the fabrication and testing of waste processing machinery; (3) educational workshops covering waste management in batik production and its environmental implications, alongside practical training in equipment usage; (4) evaluation of activity outcomes. The outcomes of this Community Service initiative include the provision of textile waste processing equipment and a heightened awareness of environmental conservation, facilitating the integration of waste processing equipment into batik production at IKM Batik Jembatan Akar.